1976
DOI: 10.1007/bf01976950
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between pea necrosis virus and bean yellow mosaic virus

Abstract: A standard pea necrosis virus isolate (PNV-E178) and two isolates resembling PNV (Kowl4 and E242) were fully compared with bean yellow mosaic virus type strain B25 (BYMV-B25). PNV-E178 and PNV-like isolates Kowl4 and E242 resembled each other and the earlier described pea necrosis strain of BYMV in their reaction on pea, but differed from BYMV strains studied so far in inclusion bodies, and in their reaction in cucumber.Serologically, PNV isolates E 178 and E242 were closely related to each other and both show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
5
11
0
Order By: Relevance
“…Our present results largely agree with those of earlier reports [3,10] with the exception that isolate E197, earlier considered a necrotic strain of BYMV, now appears to be a CYV¥ strain according to inclusion-body type, host range, and size of coat protein. The present results also confirm the earlier grouping of the pea mosaic isolate E198 as a pea (yellow) mosaic strain of BYMV [9] characterized by yellow mosaic symptoms in pea and poor pathogenicity to Phaseolus-bean genotypes.…”
Section: Discussionsupporting
confidence: 95%
“…Our present results largely agree with those of earlier reports [3,10] with the exception that isolate E197, earlier considered a necrotic strain of BYMV, now appears to be a CYV¥ strain according to inclusion-body type, host range, and size of coat protein. The present results also confirm the earlier grouping of the pea mosaic isolate E198 as a pea (yellow) mosaic strain of BYMV [9] characterized by yellow mosaic symptoms in pea and poor pathogenicity to Phaseolus-bean genotypes.…”
Section: Discussionsupporting
confidence: 95%
“…For instance, some workers regard BYMV and PMV to be strains of the same virus [4,7,20,39], while others consider them as distinct viruses [3,27]. Similarly, BYMV and CYVV are considered by some workers to be strains of the same virus [8,9,20], while others have suggested that they are distinct potyviruses [3,19,27].…”
Section: Discussionmentioning
confidence: 98%
“…Viruses do not always fit neatly into taxonomic schemes, and due to the clonal rather than sexual nature of virus reproduction, the distinction between viruses and strains will always be arbitrary. The problem is especially common in the potyvirus and tymovirus groups (Bos, 1970;Beczner et al, 1976;Koenig, 1976;Lesemann et aL, 1979). As an aid in deciding whether a 'new' entity shall be considered as a new virus or a strain of an already established virus, we would like to endorse the scheme outlined in Table 4.…”
Section: Discussionmentioning
confidence: 99%